GENETIC VARIABILITY IN THE PRNCR1 GENE AMONG A SAMPLE OF IRAQI PROSTATE CANCER PATIENTS - Kadhim, R.I.; Salman, E. D. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
The PRNCR1 gene variant among sample of Prostate Cancer (PCa) Iraqi patients case-control study was used, with PCa patients (n=32) and healthy individual control (n=33). It was successfully identified two SNPs in prostate cancer-associated noncoding RNA-1 (PRNCR-1) gene by using PCR technique and direct sequencing . The first SNP is rs13252298 (A>G) have three genotypes (AA,AG,GG )and the second SNP is rs5013678 (T> C) have three genotypes TT,TC,CC),these genotype frequencies were not in agreement with Hardy-Weinberg Equilibrium (HWE) in patients and controls .It was observed that AG genotype was more frequent in patients than controls(68.7% vs. 36.4%) with significant difference p<0.01 ,and the estimated OR of such a difference was 3.85 , this value was positive associated with PCa patients that mean this genotype AG was risk factor for PCa patients, it was also noticed that G allele in PCa patients compared with controls(40.6 vs.33.3%) show not significant difference p>0.05 . It was revealed that G allele have OR=1.16 that mean this allele have positive risk factor for PCa patients . In conclusion AG genotype for SNP rs13252298 was associated with PCa patients.